Comparative Analysis of Radar Echo Characteristics of An Extreme Hail Storm Process in East China - Xingzhi TANG; Xiaoding YU; yao YAO; Jinlan WANG (Gaoyuan qixiang)
From June 14 to the early morning of June 15， 2005， affected by the northeast cold vortex， a hail weather process rarely seen in history occurred in Shandong， northwest Jiangsu and northeast Anhui.The maximum hail diameter was 15~18 cm.Based on the new generation doppler weather radar data of 08:00 （Beijing time） from June 14 to 15， 2005， this paper compares and analyzes the radar echo characteristics of extreme hail in Shuyang， Jiangsu， Siyang and Guzhen， Anhui.Results showed that： （1） The extreme hail process in the three regions is caused by different supercells， due to the strong environmental CAPE， deep vertical wind shear and low-level relative storm helicity， the three supercells formed successively and all had strong and mosocyclones.The interaction between strong and mosocyclones and the environment leads to an upward disturbance of the pressure gradient force， which greatly increases the updraft intensity of the supercell and strong development itself.（2）The radar echo shows that the supercell causing extreme hail in the three places has high echo starting height and strong echo intensity.The maximum reflectivity factor is more than 70 dBZ， and the strong echo lasted more than 3 hours.The maximum height of 60 dBZ is higher than 11 km.In comparison， Shuyang supercell has the longest duration； Siyang supercell has the largest echo intensity； The Guzhen supercell hailstorm has the highest vertical expansion height of reflectivity factor above 60 dBZ.Preliminary clues are obtained from the above three supercell hailstorm examples： when the maximum reflectivity factor exceeds 68 dBZ and the echo expansion height of 60 dBZ is above 10 km， it indicates that extreme hail appears.（3）The bounded weak echo area （BWER） or weak echo area （WER） and the overhangs of echoes above it are the typical hailstorm structure of a supercell storm.The Siyang hailstorm showed WER and broad echo overhang， while the Shuyang and Guzhen hailstorms showed BWER and broad echo overhang.The continuous increase of mesocyclone shear value in Guzhen hailstorm is accompanied by the strong development of hailstorm.（4）The vertical integration of liquid water content （VIL） based on cells is abnormally high， reaching 88 kg·m-2， 102 kg·m-2 and 89 kg·m-2 respectively， far exceeding the VIL threshold of 65 kg·m-2 corresponding to large hail in June.The Guzhen hailstorm showed a strong storm top divergence， and the divergence velocity difference was as high as 80 m·s-1（5） There are three-body scattering spike （TBSS） in guzhen hailstorm for nearly 1 hour， and there are obvious side-lobe echo characteristics in Shuyang and Guzhen hailstorms， all indicated the existence of large hails.